Cardiac Society of Nepal (CSN) and World Heart Federation (WHF) Cardiovascular Diseases Scorecard Project - Prajapati, Dipanker; Rajbanshi, Bijoy Gopal; Adhikari, Chandra Mani; Sharma, Deewakar (Nepalese Heart Journal, 2022)
Cardiac Society of Nepal in coordination with World Heart Federation created this scorecard or Cardiovascular profile for identification of different markers for the incidence and prevalence of heart disease in Nepal. The objective of the scorecard was to understand and assess national CVD action from a civil society perspective in an effort to complement and support official government surveillance, monitoring and reporting on CVD.